Testis‐specific protein, Y‐linked 1 activates PI3K/AKT and RAS signaling pathways through suppressing IGFBP3 expression during tumor progression. Issue 5 (25th March 2019) - Tu, Wenling; Yang, Bo; Leng, Xiangyou; Pei, Xue; Xu, Jinyan; Liu, Mohan; Dong, Qiang; Tao, Dachang; Lu, Yongjie; Liu, Yunqiang; Yang, Yuan
Abstract : The testis‐specific protein, Y‐linked 1 (TSPY1), a newly recognized cancer/testis antigen, has been suggested to accelerate tumor progression. However, the mechanisms underlying TSPY1 cancer‐related function remain limited. By mining the RNA sequencing data of lung and liver tumors from The Cancer Genome Atlas, we found frequent ectopic expression of TSPY1 in lung adenocarcinoma (LUAD) and liver hepatocellular carcinoma (LIHC), and the male‐specific protein was associated with higher mortality rate and worse overall survival in patients with LUAD and LIHC. Overexpression of TSPY1 promotes cell proliferation, invasiveness, and cycle transition and inhibits apoptosis, whereas TSPY1 knockdown has the opposite effects on these cancer cell phenotypes. Transcriptomic analysis revealed the involvement of TSPY1 in PI3K/AKT and RAS signaling pathways in both LUAD and LIHC cells, which was further confirmed by the increase in the levels of phosphorylated proteins in the PI3K‐AKT and RAS signaling pathways in TSPY1‐overexpressing cancer cells, and by the suppression on the activity of these two pathways in TSPY1‐knockdown cells. Further investigation identified that TSPY1 could directly bind to the promoter of insulin growth factor binding protein 3 ( IGFBP3) to inhibit IGFBP3 expression and that downregulation of IGFBP3 increased the activity of PI3K/AKT/mTOR/BCL2 and RAS/RAF/MEK/ERK/JUN signaling in LUAD and LIHC cells. Taken together, the observations reveal a novel mechanism by which TSPY1 could contribute to the progression of LUAD and LIHC. Our finding is of importance for evaluating the potential of TSPY1 in immunotherapy of male tumor patients with TSPY1 expression. Abstract : Ectopic expression of testis‐specific protein, Y‐linked 1 (TSPY1) was associated with higher mortality rate and worse overall survival in patients with lung adenocarcinoma (LUAD) and liver hepatocellular carcinoma (LIHC). TSPY1 could directly bind to the promoter of insulin growth factor binding protein 3 (IGFBP3) to inhibit IGFBP3 expression. Downregulation of IGFBP3 increased the activity of PI3K/AKT and RAS signaling in LUAD and LIHC cells.